La ley y las costumbres. Apuntes sobre los registros civiles y los libros parroquiales en el Perú de la segunda mitad del siglo XIX (1857-1879) - Chiaramonti, Gabriela (Revista Complutense de Historia de América, 2000)
In mid-nineteenth-century Peru there were several attempts to organize the collection of trustworthy demographic data from the whole country. M.A. Fuentes, the head of the Department of Statistics was a key figure in this process. In order to achieve his aim, he tried to obtain the collaboration of ecclesiastical and civil authorities. Local priests, however, felt pressured and in their replies revealed the unfortunate state of their records of births, marriages and deaths. They also argued that the population and local and regional officials did not give them any help in preparing the information that the government requested. This article, in sum, reflects the tensions between the clergy and political authorities at a crucial time in the construction of the republican state.